Analysis of Financial Reports to Assess the Performance of Company CV Berkah Anugrah Mandiri - Siti Sri Utami; Elwardi Hasibuan; Widia Wardani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine and analyze the financial performance of CV Berkah Anugrah Mandiri whether it has shown good financial performance. The data used in this study were obtained from the Financial Statements of CV Berkah Anugrah Mandiri. Period 2018-2020. The analysis technique carried out is in the form of calculating the ratio of liquidity, solvency, activity and profitability. The results of the analysis show good financial performance from a liquidity standpoint, this can be seen from the increase in the company's current assets. The financial performance based on the solvency ratio is quite solvable, because the total assets owned by the company are quite capable and can cover all of its debts if the company is liquidated. Likewise, the ratio of the company's asset turnover to sales is quite good, this can be seen from the average ratio of total asset turnover, which is 144.76 times. The results of calculating the profitability ratios carried out on the company's financial statements CV Berkah Anugrah Mandiri during the study period showed good financial performance from the aspects of GPM, NPM, ROA and ROE